Modes of painting in the self-portraits of Marlene Dumas - Xuan, Haifeng (My University, 2012)
This MA dissertation explores modes of painting in selected self-portrait paintings by Marlene Dumas via an interdisciplinary method drawing mainly on Charles Peirce's theories on semiotics as well as Jacques Lacan's theorizing on the development of subjectivity through the so-called “mirror stage.” The research begins with the assumption that in creating/representing the self-image on the canvas, the artist is exploring his/her self. The self-portrait can thus be considered to be a means of examining the artist’s inner life. By exemplifying Lacan’s “mirror stage” alongside Peirce’s semiotic conception of the dialogical self, it also assumes that the artist engages in a dialogue with both his/herself and O(o)thers in the procedure of making the self-portrait. Such a dialogue could be regarded as a process of identification with the self and a process of constituting the self. This dissertation also proposes that the act of painting itself and the painterly surface play as important a role as the image/subject matter in viewing Dumas’ artworks. In considering Peirce’s sign theory of index and icon sign, a painting can be regarded as a kind of sign with an indexical property offering evidence of the painter’s existence. Painting can thus be described as a complex practice that engages with psychic and somatic matters of the artist. This research therefore assumes that the artist’s inner lifereading of signs is in fact always a combination of the artist and viewer, this research thus tries to establish how meaning in Dumas’ work is possible rather than what her paintings might mean. My own creative work is discussed in relation to the above concerns, such as the notion of self, the relationship between subject matter and painterly surface. How these theories affect or relate to my practical works is considered in the analyses accompanying individual works.
M.A. University of the Witwatersrand, Faculty of Humanities (Fine Arts), 2012